Rancang Bangun Aplikasi Evaluasi Belajar Untuk Persiapan Ujian Nasional Sesuai Standar Kompetensi Lulusan Berbasis Web (Studi Kasus : Sman 1 Driyorejo Gresik) - Firdausy, Ryandis Rahmatullah; Lusiani, Titik; Sutomo, Erwin (Jurnal JSIKA, 2012)
The number of graduate students in taking the National Examination (UN) is one indicator to improve the academic quality of a school. To achieve the maximum graduation, learners need to increase training so that they know how to answer the questions with correct answers and in a short time. From interviews, the length of the process of correcting lead teacher is not aware of learners who do not understand the specific material. Because not understand some of the specific materials resulting in under-prepared students to face examination. The solution is to built an application that aims to prepare students of SMAN 1 Driyorejo to better deal with the UN. This application can monitor the learning outcomes that have been given by the teacher in which there is the process of maintenance, training and value statements. Monitoring evaluation study conducted by the holding of regular exercise that teachers can know the progress of learners. With this application, students can be better prepared to face the UN. Increasing number of students who are ready to face the UN, many learners are expected to pass in the UN to improve the academic quality of SMAN 1 Driyorejo.   Keywords : Application Evaluation Study, National Examination, Graduate Competency Standards.